Content Validity of a Questionnaire to Assess Parental Involvement in Education - Caligiore Gei, María Gabriela (2021)
The objective of this study was to design an instrument to evaluate parental involvement in the education of their children, and, subsequently, to investigate the content validity of that instrument. The questions on the questionnaire have been written according to the dimensions that shape the construct of parental participation: parenting, learning supervision, communication, parental networks, and relationships with the community. Further, for the study of content validity, expert judgment has been used, and the Aiken V coefficient has been estimated. The results indicate a wide degree of agreement among the judges, showing evidence of content validity regarding the criteria of clarity, relevance, and sufficiency of the questions with Aiken V values that ranged between 0.73 and 1, with confidence intervals of 99 %. It was concluded that the instrument can be used successfully in the evaluation of parental involvement in education.